2020
DOI: 10.1097/pas.0000000000001543
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Tumor Resembling Ovarian Sex Cord Stromal Tumor (UTROSCT)

Abstract: ESR1 and GREB1 fusions have recently been described in uterine tumor resembling ovarian sex cord tumor (UTROSCT). Thus far, recurrences have been documented in a subset of those harboring GREB1 fusions, but not in those with ESR1 rearrangements. Here we describe the clinicopathologic features of 3 recurrent UTROSCTs with striking rhabdoid morphology (an unusual feature of these tumors overall) and ESR1-NCOA2 fusions. The patients were 32, 37, and 54 years at initial diagnosis and first recurrence occurred at 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(76 citation statements)
references
References 46 publications
5
71
0
Order By: Relevance
“…Of these recurrent GREB1-rearranged cases, 3/4 harbored the GREB1-NCOA2 fusions and 1/4 the GREB1-CTNNB1 fusions. Interestingly, of the 4 UTROSCT cases harboring ESR1-NCOA2 with follow up information, three cases showed recurrence, as reported by Jennifer A. Bennett et al [1,20]. In contrast, no cases showed recurrence among the 10 cases of ESR1-NCOA3 positive UTROSCT with follow up information [1].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Of these recurrent GREB1-rearranged cases, 3/4 harbored the GREB1-NCOA2 fusions and 1/4 the GREB1-CTNNB1 fusions. Interestingly, of the 4 UTROSCT cases harboring ESR1-NCOA2 with follow up information, three cases showed recurrence, as reported by Jennifer A. Bennett et al [1,20]. In contrast, no cases showed recurrence among the 10 cases of ESR1-NCOA3 positive UTROSCT with follow up information [1].…”
Section: Discussionmentioning
confidence: 62%
“…Neoplastic cells are small, round, ovoid to spindle with monotonous nuclei, inconspicuous or small to medium with distinct nucleoli, and occasionally have vascular invasion, heterologous elements, or necrosis. Recently, three cases of UTROSCTs with extensive rhabdoid differentiation and malignant behavior have been reported [20]. UTROSCTs exhibit a co-expression of epithelial, smooth muscle, sex-cord markers, and steroid receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Recurrent NCOA1-3 rearrangements in UTROSCT have been described in recent reports, with GREB1 and ESR1 as the 2 most frequent partner genes. [7][8][9] GREB1:: NCOA1, GREB1::NCOA2, ESR1::NCOA2, and ESR1:: NCOA3 fusions have all been reported in UTROSCT. In addition, CTNNB1 fused with GREB1 was reported in 1 UTROSCT.…”
mentioning
confidence: 96%
“…8,11 In addition , Bennett et al reported a series of 3 cases of UTROSCTs harboring ESR1::NCOA2 fusions, which demonstrated rhabdoid morphology and aggressive behavior. 9 One more GTF2A1::NCOA2 UTROSCT was reported with similar morphology and aggressive behavior. 12 Interestingly, some uterine sarcomas with or without ovarian sex cord differentiation also harbor GREB1 rearrangements, including GREB1::NCOA1 and GREB1::NCOA2 fusions.…”
mentioning
confidence: 98%